Mortality of a cohort of workers in Great Britain with blood lead measurements. Issue 9 (14th April 2015) - McElvenny, Damien M; Miller, Brian G; MacCalman, Laura A; Sleeuwenhoek, Anne; van Tongeren, Martie; Shepherd, Kevin; Darnton, Andrew J; Cherrie, John W
Abstract : Objectives: We examined the mortality of a historic cohort of workers in Great Britain with measured blood lead levels (BLLs). Methods: SMRs were calculated with the population of Great Britain as the external comparator. Trends in mortality with mean and maximum BLLs and assessed lead exposure were examined using Cox regression. Results: Mean follow-up length among the 9122 study participants was 29.2 years and 3466 deaths occurred. For all causes and all malignant neoplasms, the SMRs were statistically significantly raised. For disease groups of a priori interest, the SMR was significantly raised for lung cancer but not for stomach, brain, kidney, bladder or oesophageal cancers. The SMR was not increased for non-malignant kidney disease but was borderline significantly increased for circulatory diseases, for ischaemic heart disease (IHD) and cerebrovascular disease (CVD). No significant trends with exposure were observed for the cancers of interest, but for circulatory diseases and IHD, there was a statistically significant trend for increasing HR with mean and maximum BLLs. Conclusions: This study found an excess of lung cancer, although the risk was not clearly associated with increasing BLLs. It also found marginally significant excesses of IHD and CVD, the former being related to mean and maximum BLLs. The finding for IHD may have been due to lead, but could also have been due to other dust exposure associated with lead exposure and possibly tobacco smoking. Further work is required to clarify this and the carcinogenicity of lead.